Amendments suggested for zoo medical research strategies with focus on the D-A-CH region - Sipos, Wolfgang; Lutonsky, Christiane (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2021)
Objective Scientific exploration of zoo animals is one of the main missions of modern zoos. As scientific achievements are best reflected within scientific literature, we screened appropriate literature search outcomes from the 5 highest ranked zoos in the D-A-CH region (Germany-Austria-Switzerland) in order to deduce suggestions for optimizations of future research strategies.Material and methods Literature search was done by entering ”Zoo Vienna”, “Tiergarten Schönbrunn”, “Zoo Berlin”, “Tiergarten Berlin”, “Tierpark Hellabrunn”, “Tierpark Hagenbeck”, and “Zoo Zurich” on PubMed and Scopus for the period 2000–2020. These 5 European zoos were chosen due to their broad public recognition and international importance. Inclusion criterion for the literature list was the description/mentioning of analysed animals or samples with a clear affiliation to the respective zoo in the materials and methods or acknowledgements sections. Search hits were then allocated to the following 7 areas: animal nutrition, biology, ethology, infectiology, reproduction, phylogenetics, and clinical medicine. Also, portions of higher animal taxa (and species, if appropriate) were recorded.Results and conclusions A total of 142 papers has been published. Mammals, especially large ones, were clearly over-represented in literature with 2 thirds of analysed papers dealing with them. Sauropsids (birds and reptiles) were treated in 28 % and non-amniotic vertebrates (amphibians and fish) as well as invertebrates in only 3 % each. This apportionment is in no relation to the species numbers of the respective higher animal taxa. The predominating research areas (covered by approximately 75 % of papers) were ethological studies, followed by papers on infectious diseases, and finally papers on biology with morphological, physiological, and molecular biological themes. Research on reproductive biology/medicine, which is considered to be of tremendous importance for the establishment of ex-situ populations and thus for the conservation of endangered species, has been covered by only 6 % of papers. Future research should more intensely keep an eye on that discipline, especially in non-mammalian vertebrates.
Keywords: Species conservation; zoo animals; infectious diseases; reproductive medicine